Performa Konfigurasi Modul Surya Seri dan Seri Paralel pada Kondisi Mismatch Karakteristik Arus-Tegangan (I-V) terhadap Daya Output - Nurlaila Amna; Ira Devi Sara; Tarmizi Tarmizi (Jurnal Rekayasa Elektrika, 2021)
The installation of a Solar Power System (PLTS) within the ideal conditions still uses the type of solar module with the same current and voltage characteristics. However, these ideal conditions can be different if the commonly used modules are no longer available on the market. Once there is damage or interference in the operating system, such as cracks in the module plate, it will take a significantly long time to replace. This particular condition can obstruct electrical power distribution to its intended loads in the other end. Therefore, creating a robust solar panel system that operates at its maximum capacity requires an alternative or approach to find such a similar module replacement. It is expected that the replacement module will have the I-V characteristics, which relatively resemble that of the earlier module and can help to maintain the energy availability of the solar panel system. This study aims to analyze which factors affect the characteristic irregularity of currents and voltages in a solar panel installation towards the output of a solar panel under certain conditions. The solar panel system is designed using 20 solar modules with each capacity is 250 WP power that is simulated with Simulink. The method creates the mismatch condition of the current and voltage on the solar module in a specific panel configuration. These mismatch conditions are created by combining solar modules with different currents and voltages in the Series (S) and Series-Parallel (SP) configurations. The simulation is carried out by replacing the main solar module with a 5% to 100% replacement solar module. The selection of the replacement module is based on Isc, which is close to the same because the current flowing in the series circuit is the same. The simulation results showed that the solar panel system still functioned properly and produced maximum power under mismatch conditions. Of all three configurations with mismatch conditions, it is found that the best performing configuration works with the Series-Parallel (SP) configuration of the STC conditions. The maximum power which can be sustained with Series-Parallel (SP) configuration reaches up to 40% of the original modules.